Epidermal growth factor enhances spinal fusion: Posterolateral lumbar fusion model on rats - Engin Çetin; İsmail Daldal; Ali Eren; Saadet Özen Akarca Dizakar; Suna Ömeroğlu; Bora Uzuner; Hakan Hamdi Çelik; Hasan Hüseyin Saygılı; Benat Koçkar; Alpaslan Şenköylü (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to investigate the effects of human recombinant epidermal growth factor (EGF) on posterolateral lumbar fusion in a rat model. Methods: 36 male Sprague Dawley rats underwent posterolateral fusion at L4-5 level. They were randomly assigned to 3 groups: 1- Sham control group where no local augmentation was made, 2- Local Hydoxyapatite β-tricalcium phosphate (HA/β-TCP) augmentation group and 3- Local HA/β-TCP + EGF augmentation group. Rats were euthanized at 8 weeks post-surgery. 6 rats from each group were selected for manual palpation examination, micro-computed tomography analysis and histologic analysis; and the rest was used for biomechanical analysis. Results: Based on manual palpation, there was no fusion in the sham control group. Fusion rate was 33.3% in the HA/β-TCP group and 66.7% in the HA/β-TCP + EGF group (p = 0.085). Micro-CT results revealed that new bone formation was higher in the HA/β-TCP + EGF group (BV/TV: 40% vs. 65%) (p = 0.004). Histologically newly formed bone tissue was more pronounced in the EGF group and compacted and bridging bone spicules were observed. The median maximum bending moment values were 0.51 Nmm (0.42–0.59), 0.73 Nmm (0.49–0.88) and 0.91 Nmm (0.66–1.03) in the sham control, HA/β-TCP and HA/β-TCP + EGF groups, respectively (p = 0.013). The median stiffness values were 1.69 N/mm (1.12–2.18), 1.68 N/mm (1.13–2.74) and 3.10 N/mm (1.66–4.40) as in the previous order (p = 0.087). Conclusion: This study demonstrates that EGF enhances posterolateral lumbar fusion in the rat model. EGF in combination with ceramic grafts increased the fusion rates. Our findings may provide insights to further studies, investigating EGF's clinical usage as an alternative fusion enhancer. Keywords: Epidermal growth factor, Spinal fusion, Bone formation, Posterolateral fusion, Rat model